2009
DOI: 10.1111/j.1751-908x.2009.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Efficiency of Single‐Outlier Discordancy Tests for Processing Geochemical Data on Reference Materials and Application to Instrumental Calibrations by a Weighted Least‐Squares Linear Regression Model

Abstract: Numerous studies report geochemical data on reference materials (RMs) processed by outlier‐based methods that use univariate discordancy tests. However, the relative efficiency of the discordancy tests is not precisely known. We used an extensive geochemical database for thirty‐five RMs from four countries (Canada, Japan, South Africa and USA) to empirically evaluate the performance of nine single‐outlier tests with thirteen test variants. It appears that the kurtosis test (N15) is the most powerful test for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…We achieved this through the use of DODESSYS (Verma and Díaz-González, 2012) by applying all singleoutlier type tests (Barnett and Lewis, 1994;Verma, 1997Verma, , 2005Verma et al, 2009) to log-transformed ratios used in LDA by Verma and Agrawal (2011). We emphasize that discordancy tests should be applied to log-ratios and not to crude compositional data; see Verma (2012) for geochemometric reasons.…”
Section: Paleogene Faroe Islands Plateau Basaltsmentioning
confidence: 99%
“…We achieved this through the use of DODESSYS (Verma and Díaz-González, 2012) by applying all singleoutlier type tests (Barnett and Lewis, 1994;Verma, 1997Verma, , 2005Verma et al, 2009) to log-transformed ratios used in LDA by Verma and Agrawal (2011). We emphasize that discordancy tests should be applied to log-ratios and not to crude compositional data; see Verma (2012) for geochemometric reasons.…”
Section: Paleogene Faroe Islands Plateau Basaltsmentioning
confidence: 99%
“…Verma et al (2008a) simulated new critical values for these and other discordancy tests and implemented the modified version of Dixon and Grubbs test method in a computer program, DODESSYS (Discordant Outlier DEtection and Separation SYStem; Verma and Díaz-González, 2012) and named as the single-outlier type multiple-test method involving Dixon, Grubbs, skewness and kurtosis tests at 99% confidence level, initially proposed and used by Verma (1997) for processing inter-laboratory data on geochemical rock ref-erence materials. The evaluation of the relative efficiency of these single-outlier tests by Verma et al (2009) showed that the Dixon tests are less efficient than the other three types. In this method, the process of removal of outliers is iterated on the remaining dataset till there is no discordant outlier.…”
Section: Single-outlier Type Multiple Test Methodsmentioning
confidence: 99%
“…Similarly, the standard deviation values from ANOVA were lower than the literature data (2s method) for 28 elements, equal for 2 elements, and higher for 30 elements. Such differences in the mean and standard deviation values, irrespective of whether statistically significant or not, may affect the calibration of instruments or the evaluation of analytical methods (e.g., Santoyo and Verma, 2003;Guevara et al, 2005;Verma et al, 2009;Verma, 2012a).…”
Section: Comparison Of the Anova With F-t Tests And The Two Standard mentioning
confidence: 99%
“…These significance tests also require that the individual data arrays (statistical samples under evaluation) be drawn from a normal distribution (Morrison, 1990). To ascertain this assumption, we used only the multiple-outlier type tests (Barnett and Lewis, 1994;González-Ramírez et al, 2009;Verma et al, 2009) programmed in DODESSYS (Verma and Díaz-González, 2012) for identifying and separating discordant outliers at the strict 99% confidence level. We applied the ANO-VA and F tests both before and after the application of Table 13 (Appendix A -Supplementary material) presents ANOVA results for 10 major-elements (Si to P, all in %), 13 rare-earth elements (La to Lu), and 33 other trace elements (B to W).…”
Section: Applicationsmentioning
confidence: 99%